2008
DOI: 10.1128/jcm.01737-07
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Virulence Markers betweenHelicobacter pyloriStrains from Iraq and Those from Iran: Potential Importance of Regional Differences inH. pylori-Associated Disease

Abstract: Helicobacter pylori causes peptic ulceration and gastric adenocarcinoma; the latter is common in Iran but not in Iraq. We hypothesized that more virulent H. pylori strains may be found in Iran than in Iraq and so compared established and newly described virulence factors in strains from these countries. We studied 59 unselected dyspeptic patients from Iran and 49 from Iraq. cagA was found in similar proportions of strains from both countries (76% in Iran versus 71% in Iraq) and was significantly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
100
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 35 publications
22
100
9
Order By: Relevance
“…This binding activates SHP-2 and induction of stronger and longer periods of SHP-2 activity, leads to an increased signal transduction, greater morphological damage, and involved in development of gastric cancer. Therefore recent studies indicated prevalence of strains with more than one repeat region (such as ABCC) was 51.1% in Colombia and 33.3% in Italy population (20), also this current study 25.6% but in other recent studies in Iran revealed 3.3% (21) and 12% (24). This discordant as mentioned before, may be due to the high prevalence of gastric cancer and geographical and environmental difference in northern parts of Iran.…”
Section: Discussioncontrasting
confidence: 52%
“…This binding activates SHP-2 and induction of stronger and longer periods of SHP-2 activity, leads to an increased signal transduction, greater morphological damage, and involved in development of gastric cancer. Therefore recent studies indicated prevalence of strains with more than one repeat region (such as ABCC) was 51.1% in Colombia and 33.3% in Italy population (20), also this current study 25.6% but in other recent studies in Iran revealed 3.3% (21) and 12% (24). This discordant as mentioned before, may be due to the high prevalence of gastric cancer and geographical and environmental difference in northern parts of Iran.…”
Section: Discussioncontrasting
confidence: 52%
“…Such an association has previously been reported, especially in Western isolates (21). However, this relationship could not be determined in strains isolated from Asian countries (22,23). On the other hand, in a current study from Turkey, Karaman et al reported a cagA positivity rate of 65.5% and they also found a significant relationship between cagA status and peptic ulcer disease (17).…”
Section: Resultsmentioning
confidence: 58%
“…The vacA intermediate (i)-region, which encodes part of the p33 domain of VacA, displays sequence variation at the nucleotide level (Rhead et al 2007). i1-type strains, but not i2-type strain, were associated with gastric carcinoma in an Iranian population (Rhead et al 2007;Hussein et al 2008), and were an independent predictor of peptic ulcer disease in an Italian population (Basso et al 2008).…”
Section: Structure and Function Of Vacamentioning
confidence: 99%